Staging Trauma Bodies in Shadow - Haughton, Miriam (Contemporary Performance InterActions, 2018)
This book investigates contemporary British and Irish performances that stage traumatic narratives, histories, acts and encounters. It includes a range of case studies that consider the performative, cultural and political contexts for the staging and reception of sexual violence, terminal illness, environmental damage, institutionalisation and asylum. In particular, it focuses on 'bodies in shadow' in twenty-first century performance: those who are largely written out of or marginalised in dominant twentieth-century patriarchal canons of theatre and history. This volume speaks to students, scholars and artists working within contemporary theatre and performance, Irish and British studies, memory and trauma studies, feminisms, performance studies, affect and reception studies, as well as the medical humanities.